Sustainability in Construction of Commercial Buildings in Anambra State, Nigeria: Re-Orienting the Antique Construction Ethics - Chukwuebuka Martinjoe U-Dominic; Nkemakonam C. Igbokwe.N.C.; Godfrey.C. Ono; Benjamin. U. Okoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
The construction sector has a higher ratio of mass exploitation of earth reserves compared to other development sectors over time, degrading eco-components. In Anambra State, there is a high level of eco-degradation practices due to the building of commercial structures, ranging from unhealthy work plans to the inability of designers to incorporate green-culture initiatives in their designs. The objective of this study is to comprehensively evaluate the construction and operational practices of some of the functional commercial buildings in the state and ascertain the impacts of not taking sustainability considerations into account during construction. A qualitative and quantitative method of data collection was implied in the study, and the resultant findings exposed some prevalent sustainability anomalies in construction, thus igniting the need for effective and adaptive sustainable policies that would guide practices in the construction industry.